Multiple stressors drive convergent evolution of performance properties in marine macrophytes. Issue 4 (8th November 2020) - Demes, Kyle W.; Starko, Samuel; Harley, Christopher D. G.
Summary: Extreme environments have driven the evolution of some of the most inspiring adaptations in nature. In the intertidal zone of wave‐swept shores, organisms face physical forces comparable to hurricanes and must further endure thermal and desiccation stress during low tides, compromising their physiological and biomechanical performance. We examine how these multiple stressors have influenced the evolution of tissue properties during desiccation using eight phylogenetically independent pairs of intertidal and subtidal macrophytes. Intertidal species generally lost water more slowly than their subtidal counterparts, presumably as an adaption to regular emersion. Under partial desiccation, breaking force, strength, and extensibility of intertidal species generally exceeded those of subtidal species, although important differences existed among phylogenetic pairs. This was often true even when subtidal relatives resisted greater forces or were more extensible under full hydration. The interacting effects of mechanical forces and desiccation during low tide are likely a major selective agent in determining macrophyte performance and fitness. Overall, we found that lineages that have independently evolved to occupy the wave‐swept intertidal have converged on performance metrics that are likely to be adaptive to the interacting stressors associated with their extreme niches.